Evidence for movement of the alpha-amylase gene into two phylogenetically distant Bacillus stearothermophilus strains. - Satoh, H (1988)
The gene for an alpha-amylase cloned from strain DY-5 of Bacillus stearothermophilus was used to examine to what extent the corresponding genes are structurally similar in other B. stearothermophilus strains. The structure of the gene itself was almost identical in DY-5 and a group of strains represented by strain 799. The gene was not detected at all in strain DSM2334, which was phenotypically amylase deficient. Comparison of the structure of 5S rRNA and electrophoretic pattern of the ribosomal proteins indicates that strains DY-5 and DSM2334 are closely related to each other, whereas strain 799 is phylogenetically very distant from the two. We estimate that strain 799 separated from DY-5 and DSM2334 some 420 million years ago. Nucleotide sequencing of the region containing the amylase gene from strains DY-5 and 799 revealed the presence of a 3.4-kilobase stretch that was highly similar in the two strains. Furthermore, comparison of the restriction map surrounding the amylase gene of DY-5 with that of a corresponding region in DSM2334 indicated that the former strain contained an extra segment 5.5 kilobases in length, which included the 3.4-kilobase stretch mentioned above. This segment was missing in DSM2334. It thus appears that the alpha-amylase gene was brought into strains DY-5 and 799 from outside despite a large phylogenetic distance.